The Influence of Accounting Information System on the Organizational Performance Among SMEs in Tagum City - Burgos, Chrisha P.; Namoc, Irish S.; Padilla, Jasmeren P.; Flores, Joe Mari N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Accounting Information System serves as a mechanism for enhancing better organizational performance. The study intends to determine the influence of accounting information systems on the organizational performance among SMEs in Tagum City by evaluating the level of accounting information systems in terms of system quality, information quality, and system threats, and the level of organizational performance in terms of organizational efficiency, cost reduction, and quality of decision making of the small-medium enterprises in Tagum City. Also, it aims to determine the significant relationship between the accounting information system and the organizational performance of SMEs. A quantitative and descriptive-correlational method is used, through the adapted survey questionnaires where 240 SMEs in Tagum City responded. The results were tested at a 0.05 level of significance. System quality and information quality have the highest level (4.37 mean, 0.386 SD), and (4.35 mean, 0.392 SD). System threat has a low level (2.40 mean, 0.426 SD). Cost reduction, quality of decision-making, and organizational efficiency have a very high level (4.47 mean, 0.424 SD; 4.41 mean, 0.393 SD; 4.38 mean, 0.389 SD). The results revealed that accounting information system versus organizational performance yields an R-value of 0.709, which means significant. The outcome is due to the p-value of 0.000, lower than 0.05 levels of significance. It led to the decision that the null hypothesis, which stated no significant relationship between accounting information systems and organizational performance, was rejected. Therefore, the correlation result exemplifies that the accounting information system on SMEs organizational performance in Tagum City is very high.